Rechtvaardiging en recht in de kerk: Over de theologische achtergronden van het gereformeerde kerkrecht - Spijker, Willem van't (Hervormde teologiese studies, 1992)
Justification and law in the church: The theological background of reformed church law In reformed church law there is a connection between ecclesiastical structure (disciplina) and ecclesiastical doctrine (doctrina). Luther’s doctrine of justification disrupted the hierarchical structure of the church. For him, whose conception of the church started from the principle of the unique priesthood of Christ, church law was ius divinum. The Calvinists paid more attention to the church and her organisation than Luther did. Because they related the church order to the ordo salutis, the church came to serve the true doctrine, which is her primary characteristic.